Targeting autophagy in HCC treatment: exploiting the CD147 internalization pathway - Meirui Qian; Ziyu Wan; Xue Liang; Lin Jing; Huijie Zhang; Heyao Qin; Wenli Duan; Ruo Chen; Tianjiao Zhang; Qian He; Meng Lu; Jianli Jiang (Cell Communication and Signaling)
Abstract Background/Aims Chemotherapy resistance in liver cancer is a major clinical issue, with CD147 playing a vital role in this process. However, the specific mechanisms underlying these processes remain largely unknown. This study investigates how CD147 internalization leads to cytoprotective autophagy, contributing to chemotherapy resistance in hepatocellular carcinoma (HCC). Methods Utilizing bioinformatics methods for KEGG pathways enrichment and screening key molecules associated with chemotherapy resistance through analyses of GEO and TCGA databases. An overexpression/knockdown system was used to study how CD147 internalization leads to autophagy in vitro and in vivo. The process was observed using microscopes, and molecular interactions and autophagy flux were analyzed. Analyzing the internalization of CD147 intracellular domains and the interaction with G3BP1 in clinical chemotherapy recurrence HCC tissues by immunohistochemistry, tissue immunofluorescence, and mass spectrometry. A tumor xenograft mice model was used to study cytoprotective autophagy induced by CD147 and test the effectiveness of combining cisplatin with an autophagy inhibitor in nude mice models. Results In our study, we identified the tumor-associated membrane protein CD147, which implicated in chemoresistance lysosome pathways, by evaluating its protein degree value and betweenness centrality using Cytoscape. Our findings revealed that CD147 undergoes internalization and interacts with G3BP1 following treatment with cisplatin and methyl-β-cyclodextrin, forming a complex that is transported to lysosomes via Rab7A. Notably, higher doses of cisplatin enhanced CD147-mediated lysosomal transport while concurrently inhibiting SG assembly. The CD147-G3BP1 complex additionally inhibits mTOR activity, promoting autophagy and augmenting chemoresistance in hepatoma cells. In vivo studies investigations and analyses of clinical samples revealed that elevated internalization of CD147 is associated with chemotherapy recurrence in liver cancer and the maintenance of stem cells. Mice experiments found that the combined administration of cisplatin and hydroxychloroquine enhanced the efficacy of treatment. Conclusions This study reveals that CD147 internalization and CD147-G3BP1 complex translocation to lysosomes induce cytoprotective autophagy, reducing chemotherapy sensitivity by suppressing mTOR activity. It is also shown that chemotherapy drugs combined with autophagy inhibitors can improve the therapeutic effect of cancer, providing new insights into potential targeted therapeutic approaches in treating HCC.